Combustion and emissions characteristics of a compression ignition engine fueled with n-butanol blends. Issue 1 (November 2015) - Yusri, I M; Mamat, R; Ali, O M; Aziz, A; Akasyah, M K; Kamarulzaman, M K; Ihsan, C K; Mahmadul, H M; Rosdi, S M
Abstract: The use of biomass based renewable fuel, n-butanol blends for compression ignition (CI) engine has attracted wide attention due to its superior properties such as better miscibility, higher energy content, and cetane number. In this present study the use of n-butanol 10% blends (Bu10) with diesel fuel has been tested using 4-cylinder, 4-stroke common rail direct injection CI engine to investigate the combustion and emissions of the blended fuels. Based on the tested engine at BMEP=3.5Bar Bu10 fuel indicates lower first and second peak pressure by 5.4% and 2.4% for engine speed 1000rpm and 4.4% and 2.1% for engine speed 2500rpm compared to diesel fuel respectively. Percentage reduction relative to diesel fuel at engine speeds 1000rpm and 2500rpm for Bu10: Exhaust temperature was 7.5% and 5.2% respectively; Nitrogen oxides (NOx ) 73.4% and 11.3% respectively.